Technical Efficiency and Production Determinants of Household-scale Grape Farming in an Agritourism Village of Ciganjeng, Pangandaran, Indonesia - Umbara, Dona Setia; Jakiyah, Ulpah (Universitas Panji Sakti, 2025)
The establishment of a tourist village with grapes as a tourist attraction in a suboptimal area is strongly influenced by the level of efficiency, both technically and economically. Suboptimal land in Pangandaran Regency is characterized by dryness, so inefficiency in input use can lead to low production and productivity levels in grape cultivation. Furthermore, the presence of a tourist village has an impact on the social life of the local community. The purpose of this study was to determine the factors that influence grape cultivation as an agritourism activity. In addition, to measure the technical and economic efficiency of grape cultivation at the household scale. The method used in this study was parametric statistics with the Stochastic Frontier Analysis approach. The sample was selected through purposive sampling, comprising 60 respondents who cultivate plants. The research respondents were selected with the criteria of farmers who have grown grapes for more than 2 years. The results showed that the level of efficiency of grape cultivation in the yard has a technical efficiency value of 0.856. Factors that influence the level of technical efficiency are the number of trees, the amount of manure, the amount of growth fertilizer, and labor. Meanwhile, the socioeconomic factor that influences the level of technical inefficiency is the age of the farmer. The age of the farmer has a significant impact on the level of inefficiency in grape cultivation activities. The recommendation from this research is that input subsidy programs, such as compost fertilizer, should continue to be provided to grape farmers. Comparative studies with other tourist villages should be conducted to obtain market information. Additionally, training programs for the young generation in grape cultivation should be implemented to maintain agrotourism.